2004
DOI: 10.1038/sj.npp.1300623
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Brain White Matter Microstructure by Excessive Intracellular and Extracellular Fluid in Alcoholism: Evidence from Diffusion Tensor Imaging

Abstract: Magnetic resonance diffusion tensor imaging (DTI) has revealed the disruption of brain white matter microstructure in normal aging and alcoholism undetectable with conventional structural MR imaging. The metrics of DTI can be useful in establishing the nature of the observed microstructural aberrations. Abnormally low fractional anisotropy (FA), a measure of diffusion orientation and coherence, may result from increased intracellular or extracellular fluid, which would be reflected in complementary high appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
124
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 197 publications
(144 citation statements)
references
References 57 publications
16
124
0
1
Order By: Relevance
“…In agreement with other rodent (Harsan, et al, 2006) and human (Huisman, et al, 2006;Nakayama, et al, 2006;Persson, et al, 2006;Pfefferbaum & Sullivan, 2005) studies, FA values observed herein were higher in the splenium than the genu, suggesting across-species consistency in white matter microstructural quality. The FA values for the corpus callosum reported here from both ROI and fiber tracking analyses fall within the range of published values in rodents from ROI analysis (range: 32 to 75%) (Guilfoyle, et al, 2003;Harsan, et al, 2006;Nair, et al, 2005;Tyszka, et al, 2006;Verma, et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…In agreement with other rodent (Harsan, et al, 2006) and human (Huisman, et al, 2006;Nakayama, et al, 2006;Persson, et al, 2006;Pfefferbaum & Sullivan, 2005) studies, FA values observed herein were higher in the splenium than the genu, suggesting across-species consistency in white matter microstructural quality. The FA values for the corpus callosum reported here from both ROI and fiber tracking analyses fall within the range of published values in rodents from ROI analysis (range: 32 to 75%) (Guilfoyle, et al, 2003;Harsan, et al, 2006;Nair, et al, 2005;Tyszka, et al, 2006;Verma, et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…As social disturbances are highly involved in relapse (Zywiak et al, 2003;Uekermann and Daum, 2008), our results suggest that this link between frontal alterations and relapse could be partly due to this inability to regulate social problems when frontal areas are damaged; (b) altered frontocingulate functional connectivity. Several studies showed white matter abnormalities in alcohol-dependence (Pfefferbaum and Sullivan, 2005), which are correlated with higher relapse rates (Sorg et al, 2012). This study, being among the first ones to use PPI analyses in alcohol-dependence, extends these previous results by identifying the functional correlates of structural white matter impairments: these impairments notably lead to altered frontocingulate connectivity, hampering the cognitive regulation of social exclusion feelings and potentially increasing relapse risk.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, the analysis criteria applied in fiber tracking serve as a form of erosion of voxels with a high potential of containing non-white matter signal. The resulting regionally differential increase in water motility with age is likely attributable to age-related increases in extracellular spaces (Sen and Basser, 2005) but cannot currently be definitively discerned in vivo (e.g., Norris et al, 1994;Pfefferbaum and Sullivan, 2005b;Rumpel et al, 1998;Sehy et al, 2002;Silva et al, 2002). It may also reflect breakdown of myelin sheathing, trapping of fluid between thin or lysed sheathes and between fibers and bulbous swelling of oligodendrocytes observed postmortem in normal aging human and nonhuman primates Sethares, 2002, 2003;Peters et al, 2001).…”
Section: Discussionmentioning
confidence: 99%